2019
DOI: 10.1177/2280800019851764
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of nanohydroxyapatite synthesized from eggshell waste in occluding dentin tubules

Abstract: Objectives: Dentin hypersensitivity (DH) is a notable painful condition with a negative impact on quality of life. This paper evaluates the occluding abilities of nanohydroxyapatite synthesized from the eggshell waste (EnHAp) in the treatment of DH. Methods: EnHAp was synthesized following the wet chemical precipitation method. The purity and phase change were characterized using Fourier transform infrared (FTIR) and X-ray diffraction (XRD). Field emission scanning electron microscopy (FESEM) and high-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…12 An irregular-red like structure with a slightly higher particle size of 80 to 100 nm, were, however, observed in another study. 20 The difference in the morphology observed in both studies may be attributed to the preparation technique.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…12 An irregular-red like structure with a slightly higher particle size of 80 to 100 nm, were, however, observed in another study. 20 The difference in the morphology observed in both studies may be attributed to the preparation technique.…”
Section: Resultsmentioning
confidence: 88%
“…This may likely be attributed to the solubility of the calcined eggshell in the deionized water, and or the absence phosphate group. 20 On the contrary, the samples treated with nHAp shows complete remineralization of the dentine tubules (Figure 7(e)). This is in agreement with several randomized clinical trials that confirmed the remineralization characteristics of nHAp.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations